Study on Dynamic Characteristic of Cylindrical Roller Bearing at Start-stop Process - Tu Wenbing; He Haibin; Liu Leping; Luo Ya (Jixie chuandong)
The start-stop process generally exists in rotating machinery,and the speed change of the process has a great influence on the dynamic performance of rolling bearing,while the study on the dynamic characteristics of rolling bearing in the start-stop process is relatively lack. Taking cylindrical roller bearing NU306 as investigation object,a three-dimensional dynamic FEM for nonlinear contact cylindrical roller bearing is established. Based on explicit dynamics finite element method,the dynamic simulations of cylindrical roller bearing in the start-stop process for different angular acceleration and different radial load conditions are carried out. The influence of angular acceleration and radial load on its dynamic characteristics in the start-stop process are studied,which are the angular velocity of cage,and the centroid displacement of inner ring and the contact force between rollers and cage,and the experimental verification is carried out. The study results show that the increase of the inner ring angular acceleration will increase the slip of rolling bearing in the start-stop process,and the increase of radial force will reduce the slip of rolling bearing in the start-stop process,and in the start-stop process,the greater the angular acceleration and radial force,the greater the centroid displacement of inner ring and contact force between rollers and cage. The simulation results are in good agreement with the experimental results,and the validity of the finite element model is verified.